The boy in the drawer - Munsch, Robert N., 1945-; Martchenko, Michael (Toronto ; Annick Press ; Buffalo, NY, 1986)
One day Shelley discovers socks all over her bedroom and then finds a tiny boy in her sock drawer.
3.0
K-3
K-3
420L
Keywords: Humorous stories; Humorous fiction